Detection of virulence factors of Escherichia coli focused on prevalence of EAST1 toxin in stool of diarrheic and non-diarrheic piglets and presence of adhesion involving virulence factors in astA positive strains - Zajacova, Zuzana Sramkova; Konstantinova, Lucie; Alexa, Pavel (Veterinary microbiology, 2012)
Between 2005 and 2009, a total of 800 Escherichia coli strains isolated from piglets with diarrhea were tested for the presence of enteroaggregative heat-stable enterotoxin EAST1, heat-labile (LT) and heat-stable enterotoxins (STa) and shigatoxin (Stx2e) by PCR with the purpose of investigating the present distribution of virulence factors on swine farms in the Czech Republic. The isolates were analyzed for their O-serogroup, fimbrial (K88, K99, 987P, F41, F18) and nonfimbrial adhesins (adhesin involved in diffuse adherence AIDA and porcine attaching and effacing-associated factor PAA). The detection rates of ETEC and STEC isolates were 36.5% and 7.75%, respectively, which implies that ETEC play the major role in E. coli infections in Czech herds. Generally, the most common serotype was O149:K88 which possessed genetic determinants for LT and EAST1. None of the tested E. coli isolates was positive for genes K99, 987P and F41. It was shown that out of 800 E. coli strains isolated from pigs, 277 were EAST1 positive and 74% from the latter were identified as ETEC. Of the fimbrial adhesins, K88 and F18 were commonly detected. Over 80% of K88/EAST1 positive strains possessed the gene for paa. We detected no EAE isolate positive for fimbrial adhesins or PAA and AIDA. The AIDA was more often associated with F18 than with K88. The gene astA was also identified among E. coli isolates of non-diarrheic piglets. We tested rectal swab samples collected from apparently healthy piglets on three farms. On all farms, E. coli astA positive strains (26.66%, 90.00% and 46.66% astA positive animals) were isolated. Our results showed a significantly higher prevalence of astA positive E. coli isolates among apparently healthy piglets in comparison with diarrheic piglets. The question remains as to what is the role of the astA gene in the pathogenesis of porcine colibacillosis and as a virulence factor.
Keywords: Feces; Prevalence; Virulence Factors; proteiny z Escherichia coli; Bacterial Adhesion; Česká republika; polymerázová řetězová reakce; Polymerase Chain Reaction; virulence; prevalence; Enterotoxins; bakteriální adheze; Czech Republic; Swine Diseases; nemoci prasat; Swine; Fimbriae, Bacterial; Shiga Toxin; Escherichia coli; Diarrhea; Enterotoxigenic Escherichia coli; zvířata; feces; Virulence; shiga toxin; Escherichia coli Proteins; bakteriální fimbrie; Escherichia coli Infections; průjem; prasata; enterotoxiny; enterotoxigenní Escherichia coli; Adhesins, Bacterial; faktory virulence; bakteriální adheziny; infekce vyvolané Escherichia coli; Animals